Peningkatan Motorik Kasar Melalui Permainan Ucak Inovatif - Putri Ramadhani, Selmita; Ismet, Syahrul (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Learning was more focused on fine motor development, while gross motor learning received less attention and teaching methods related to gross motor skills in children were carried out monotonously which made children bored with the activity. This study aims to determine the improvement of children's gross motor skills through innovative ucak games at Taman Kanak-kanak Harapan Bunda Kecamatan Talawi Kota Sawahlunto. The type of research used was Classroom Action Research (CAR). The subjects in this study were children at Taman Kanak-kanak Harapan Bunda Kecamatan Talawi Kota Sawahlunto. The study was conducted in a class with 10 students. This study was carried out in several cycles consisting of four main stages: planning, implementing actions, observation, and reflection. Based on the results of the study, the results of innovative ucak games were able to improve children's gross motor skills as seen from the following assessments: Children's ability to pass through the game track by walking and tiptoeing has increased from the previous percentage of only 2% to 80%. The child's ability to jump according to the exemplified movements increased from 20% to 90%. The child's ability to maintain balance while jumping increased from 10% to 80%. The child's ability to throw objects according to the target box pattern in the game increased from 20% to 80%. The child's ability to move quickly and flexibly during the game increased from 10% to 80%.